Dampak Mediasi Loyalitas Kerja pada Lingkungan, Motivasi, Kompensasi dan Kepuasan Kerja terhadap Kinerja Karyawan - Ustadus Sholihin; Ririn Wahyu Arida (Universitas Medan Area, 2021)
This study aims to analyze the impact of the work environment, employee motivation, company compensation, and job satisfaction on employee performance through employee work loyalty as a mediating variable at the Melinda Kediri Mother and Child Hospital (RSIA). This study used a sample of 50 employees. The sampling technique used is the saturated sampling technique. Data collection techniques using primary and secondary data. The data analysis technique used is Path Analysis and is supported by Sobel test calculations. The results of the research analysis show that based on the regression equation model 1 environment, motivation, compensation and job satisfaction have a positive and significant influence on employee work loyalty. Based on the regression equation model 2, environment, motivation, compensation and job satisfaction are not significant on employee performance, while employee work loyalty has a significant positive effect on employee performance. Based on the regression equation model 1 and 2, loyalty is able to mediate the influence of the environment, motivation, compensation and job satisfaction on the performance of the employees of the Melinda Kediri Mother and Child Hospital (RSIA)